Six new Orchestina species from Hainan Island, China (Araneae, Oonopidae) - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2011)
Six new species of the genus Orchestina are described: O. aureola sp. nov., O. clavulata sp. nov., O. truncatula sp. nov., O. tubulata sp. nov., O. yinggezui sp. nov. and O. zhengi sp. nov. All species were collected on Hainan Island (China) by canopy fogging.